The Reappearance of Menstruation After Childbirth Associated with Contraceptive Use Among Women of Reproductive Age in Kyrgyzstan - Nuraeni, Tating; Yunus, Mohd; Supriatin, Supriatin (JURNAL INFO KESEHATAN, 2025)
The return of menstruation after childbirth is an important aspect of women's reproductive health, especially in the context of contraceptive use. This study aims to explore how the return of menstruation after childbirth is closely connected to contraceptive use, with various factors such as age, marital status, region, place of residence, education level, ethnicity, and wealth index in Kyrgyzstan playing a role.  This study employed secondary data from the Kyrgyzstan 2023 Multiple Indicator Cluster Survey (MICS), focusing on women of reproductive age (15-49 years). The analysis utilized a final sample of 1.059 women and applied binary logistic regression to examine the relationship between contraceptive use and the return of menstruation after childbirth while controlling for factors such as age, marital status, region, education level, ethnicity, and wealth index. The study found that among 1.059 women who had given birth, 30.88% were using contraceptive methods, and 64.68% experienced the return of menstruation post-childbirth. The multivariate analysis indicates that menstrual return after giving birth, having marital status formerly married/in union, in Naryn, Talas, and Chui region, and having the richest wealth index significantly influence contraceptive use among women of reproductive age. These results underscore the importance of comprehensive sexual health education, improved healthcare services, and targeted communication strategies to increase contraceptive use in the region.